Revisiting Italian Emigration Before the Great War: A Test of the Standard Economic Model - Pier Giorgio Ardeni; Andrea Gentili (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
Among the many studies on migration before the Great War, Italy has received little attention, with a few notable exceptions and without providing a convincing explanation of its economic and demographic determinants. Standard neoclassical approaches explain emigration as driven by relative wages, relative employment rates and the stock of previous emigrants. We aim at improving on earlier contributions by covering all migration outflows from Italy to the most significant destination countries and by adopting the most consistent and up-to-date econometric approaches. As it turns out, the standard model is not fully confirmed and a more nuanced analysis is needed.
Keywords: F22; N32; 330